Generating art from the agricultural sciences: looking inside the everyday territory - Díaz Medina, Andrea Valentina (Universidad Pedagógica y Tecnológica de Colombia, 2023)
For agricultural sciences, the photographic image has been a relevant tool, not only to record what the eye perceives, but as a multidisciplinary technical element, generator of knowledge, and presenter of speeches. For this reason, this collective plastic exhibition brought together 36 images achieved in practice-teaching-learning processes, from walking, to field trips, as a result of observing and analyzing human constructions in the landscape. The field of agricultural sciences has greatly benefited from the use of photographic images, not only as a tool for capturing visual information but also as a multidisciplinary technical element that generates knowledge and presents ideas. To showcase this, a collective exhibition of 36 images has been organized, which were taken during practical teaching and learning processes such as field trips. These images were captured while observing and analyzing the man-made constructions within the landscape. The text describes three thematic resonances, including the 'rural extension of productive landscapes' and photographs of rural geographical territories that showcase the country's productive diversity. It also references a space for aesthetics and culture, using the image of skies reflected in the river and highlighting the co-inhabitants of the territory, such as pollinators, with their rapid flapping flight, detailed jump, and anxious wait.“Social context of agriculture”, referring to the farmer and the space carved out around the crop, the working conditions, customs and identities, and the hands that show the attachment and sacrifice for rural work. Beings remembered through the seeds, fruits, and colors of the earth, which invite us to reflect on Agri-Culture as the habitation that allows us to remain.“Agricultural machinery”, alluding to the novelty in the countryside landscape, the machinery that reflects innovation, research processes, or manual work that is not abandoned, the call to the traditional among the absences of and with the farmer. Approaching the photographic image as an investigative matter enables observation, analysis, and theorization of social reality. The image as testimony contextualizes observations, deepens field experiences, and creates realities.With these thoughts of change, work, and study, we consider the new fields and peasants, traditions and forgetfulness, in the city nestled among the foliage. Thus, in our food spheres and territories, new ways of experimenting and expressing ourselves are emerging. We contemplate the technicalization of existence and the power of generating knowledge through photography.